The relationship between diet and events Gastroesophageal Reflux Disease (GERD) inteenager - Nasution, Nurromsyah; Satria, Orita (Journal of Midwifery and Nursing, 2025)
Heartburn (epigastric pain), acid regurgitation (gastric pain), nausea, and dysphagia are some of the symptoms of gastroesophageal reflux disease (GERD), a disorder in which stomach acid refluxes into the esophagus. Because it can cause digestive disorders in adolescents, diet is considered a risk factor for GERD. The approach used was cross-sectional, and sample selection was carried out through cluster random sampling of 40 respondents. The location of the study was at the Alue Pisang Health Center, Southwest Aceh, August–November 2024. The results of the bivariate analysis between diet and GERD symptoms in adolescents showed a relationship between the two, with a p value of 0.000 (P <0.05). The health center is expected to promote education about GERD prevention in schools